Blockage of BCL-XL overcomes venetoclax resistance across BCL2+ lymphoid malignancies irrespective of BIM status - Dolnikova, Alexandra; Kazantsev, Dmitry; Klanova, Magdalena; Pokorna, Eva; Sovilj, Dana; Kelemen, Cristina Daniela; Tuskova, Liliana; Hoferkova, Eva; Mraz, Marek; Helman, Karel; Curik, Nikola; Machova Polakova, Katerina; et al. (Blood advances, 2024)
Venetoclax (VEN), a B-cell lymphoma 2 (BCL2) inhibitor, has a promising single-agent activity in mantle cell lymphoma (MCL), acute lymphoblastic leukemia (ALL), and large BCLs, but remissions were generally short, which call for rational drug combinations. Using a panel of 21 lymphoma and leukemia cell lines and 28 primary samples, we demonstrated strong synergy between VEN and A1155463, a BCL-XL inhibitor. Immunoprecipitation experiments and studies on clones with knockout of expression or transgenic expression of BCL-XL confirmed its key role in mediating inherent and acquired VEN resistance. Of note, the VEN and A1155463 combination was synthetically lethal even in the cell lines with lack of expression of the proapoptotic BCL2L11/BIM and in the derived clones with genetic knockout of BCL2L11/BIM. This is clinically important because BCL2L11/BIM deletion, downregulation, or sequestration results in VEN resistance. Immunoprecipitation experiments further suggested that the proapoptotic effector BAX belongs to principal mediators of the VEN and A1155463 mode of action in the BIM-deficient cells. Lastly, the efficacy of the new proapoptotic combination was confirmed in vivo on a panel of 9 patient-derived lymphoma xenografts models including MCL (n = 3), B-ALL (n = 2), T-ALL (n = 1), and diffuse large BCL (n = 3). Because continuous inhibition of BCL-XL causes thrombocytopenia, we proposed and tested an interrupted 4 days on/3 days off treatment regimen, which retained the desired antitumor synergy with manageable platelet toxicity. The proposed VEN and A1155463 combination represents an innovative chemotherapy-free regimen with significant preclinical activity across diverse BCL2+ hematologic malignancies irrespective of the BCL2L11/BIM status.
Keywords: apoptóza; protoonkogenní proteiny c-bcl-2; lidé; Isoquinolines; Xenograft Model Antitumor Assays; sulfonamidy; Benzothiazoles; Apoptosis; Drug Synergism; chemorezistence; Drug Resistance, Neoplasm; Cell Line, Tumor; Antineoplastic Agents; Proto-Oncogene Proteins c-bcl-2; protinádorové látky; myši; Humans; Mice; isochinoliny; benzothiazoly; synergismus léků; zvířata; Sulfonamides; protein BCL2L11; bcl-X Protein; Animals; xenogenní modely - testy protinádorové aktivity; nádorové buněčné linie; Bcl-2-Like Protein 11; protein bcl-X; Bridged Bicyclo Compounds, Heterocyclic; bicyklické sloučeniny heterocyklické